ANALISIS SWOT PADA PEMBELAJARAN TEMATIK - Triyono, Triyono; Wiyani, Novan Ardy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This Integrated learning is said to be child-centered learning because basically integrated learning is a learning system that provides flexibility to students, both individually and in groups. Students can actively seek, explore, and find concepts and principles of knowledge that must be mastered according to their development. Students will understand their learning outcomes according to the facts and events they experience, not just information from the teacher. Teachers act more as facilitators and catalysts who guide towards the goals to be achieved. Meanwhile, students are actors who seek facts and information to develop their knowledge. This study aims to analyze the implementation of integrated learning at MI Muhammadiyah Kembaran Wetan, Kaligondang District, Purbalingga Regency using SWOT analysis. The results showed various advantages from the side of the school principal and teachers, and deficiencies were found in terms of the difficulty of the teacher in linking various subjects and still tended to use the conventional approach. Learning tools and media are also still very minimal. Various opportunities have been inventoried as a reference for learning development. Improving the quality of teachers in their ability to use available teaching materials is a challenge that must be bridged